Handwashing as a risk factor for increasing ventilator associated pneumonia (VAP) incidence at Sanglah Hospital, Denpasar, 2012 - Abdul Azis; Anak Agung Sagung Sawitri; Ketut Tuti Parwati Merati (Universitas Udayana, 2013)
Ventilator associated pneumonia (VAP) is a lower respiratory tract nosocomial infection which frequently resulted from mechanical ventilation support of more than 48 hours in an intensive care unit (ICU). The incidence of VAP at Sanglah Hospital is 15.48 per 1000 days used still higher than the national standard of 10 per 1000 days used. Risk factors for VAP transmission include host condition, medical equipment hygiene and healthcare provider behaviors, including handwashing. This study aimed to analyze contributing risk factors for VAP incidence at Sanglah Hospital, specifically handwashing procedures. Study applied a case control design with 27 cases (those with VAP) and 54 controls (non-VAP), from similar gender and age backgrounds. Case control data was obtained from medical records of 2012. Data from healthcare providers (doctors and nurses attending to the study population) was obtained through interviewing using structure questionnaires and cross checking through assessment of medical records. The univariate and bivariate data was analyzed by chi square and multivariate by logistic regression. Findings indicated that the contributing factors are healthcare provider handwashing (OR=6.11; 95%CI: 1.54-24.25), length of hospital stay (OR=4.18; 95%CI: 1.36-12.81) and associated disease (OR=4.22; 95%CI: 0.98-18.25). Nurse behaviors contributed to VAP incidence (OR=4.69; 95%CI: 1.22-18.08). Doctors indicated difficulty in adhering to handwashing protocol (the 5 moment handwashing requirements) particularly before aseptic procedure (45,1% in cases and 66,3% in control). Study indicates that poor handwashing behaviors contribute to VAP incidence. There is a need for health promotion initiatives that encourage adherence to official handwashing protocol